What Makes Currencies Volatile? An Empirical Investigation - Bleaney, Michael (2012)
Real effective exchange rate volatility is examined for 90 countries using monthly data from January 1990 to June 2006. Volatility decreases with openness to international trade and per capita GDP, and increases with inflation, particularly under a horizontal peg or band, and with terms-of-trade volatility. The choice of exchange rate regime matters. After controlling for these effects, an independent float adds at least 45% to the standard deviation of the real effective exchange rate, relative to a conventional peg, but most other regimes make little difference. The results are robust to alternative volatility measures and to sample selection bias.